Private Discount Premium - Why Non Public Companies are Negotiated at Lower Relative Prices - Pavao, Breno (2020)
The current study proposes a model based on CAPM and valuation multipliers to capture the risk for privately held companies with the information normally available for it. The main assumption is that the relative price differential between the average private and public company reflects all additional risk brought by the private market, this difference is then annualized through dividend discount model to be in the same terms as other CAPM’s variables. Then a possible justification for this premium is done through liquidity differentials, the premise is that liquidity is driven mainly by number of market participants which makes the market more efficient and the supply and demand dynamics balanced, creating an environment where assets are traded closer to their intrinsic value. Private markets by their own nature are riskier and present higher degree of information asymmetry, this would drive away investors not willing to be exposed to such risk and would decrease the market liquidity and overall asset prices with it. To test for this hypothesis, a correlation analysis of market participant’s proxy indicators and the observed premium is done.